2021
DOI: 10.3892/etm.2021.10334
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 gene expression changes in the placentas of women smokers

Abstract: The placenta can be affected by environmental factors, such as exposure to cigarette smoke. This exposure in the fetal context is considered a risk factor for the development of short-term postnatal diseases, such as asthma. Asthma is an inflammatory disease characterized by predominant acquisition of CD4 T lymphocytes (TLs) of the Th2 type. Transcription factors such as GATA binding protein 3 (GATA3) and STAT6 actively participate in the differentiation of virgin TLs towards the Th2 profile, while transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Runx1 appears to play an important role in murine decidual development and the interaction of the decidua with invading trophoblast (Kannan et al, 2023). In the human placenta RUNX1 protein was observed in chorionic villi and decidua (Bermudez et al, 2021) but in the absence of co-labeling, cell type localization could not be confirmed. By contrast, the findings of Ponder et al point specifically to the presence of RUNX1 protein in cell column CTB and EVT throughout gestation (Ponder et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Runx1 appears to play an important role in murine decidual development and the interaction of the decidua with invading trophoblast (Kannan et al, 2023). In the human placenta RUNX1 protein was observed in chorionic villi and decidua (Bermudez et al, 2021) but in the absence of co-labeling, cell type localization could not be confirmed. By contrast, the findings of Ponder et al point specifically to the presence of RUNX1 protein in cell column CTB and EVT throughout gestation (Ponder et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Transcription factor RUNX2 is considered the master regulator of osteoblastic differentiation in humans by regulating multiple signaling pathways and transcriptional activation of a series of downstream molecules [ 8 ]. RUNX2 is closely related to the proliferation, invasion, and bone metastasis in multiple cancer types, such as osteosarcoma, breast cancer (BC), prostate cancer, gastric cancer, colorectal cancer, and lung cancer [ 7 10 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of Cell Biology of a series of downstream molecules [8]. RUNX2 is closely related to the proliferation, invasion, and bone metastasis in multiple cancer types, such as osteosarcoma, breast cancer (BC), prostate cancer, gastric cancer, colorectal cancer, and lung cancer [7][8][9][10]18]. Lung cancer causes the highest number of cancer-related deaths worldwide [19].…”
Section: Discussionmentioning
confidence: 99%